English Verb-particle Constructions: Two Types, Two Structures - Zoerner, Ed (Kansas Working Papers in Linguistics, 1996)
This paper proposes that resultative verb-particle constructions (VPCs) have an underlyingly different structure from idiomatic VPCs; both structures differ from the Small Clause analysis of Kayne (1985) et al and the verb-particle complex analysis of Johnson (1991). Empirical support for the new proposal comes from anaphor deletion facts and coordination facts. The analysis also accounts for previously noted data involving VPCs.